A bug in enantiomer separation: double salt formation – diastereomeric and double salt structures of 1-cyclohexylethylammonium 2- and 4-chloromandelate. Issue 31 (16th July 2021) - Bereczki, Laura; Zodge, Amit; Kőrösi, Márton; Holczbauer, Tamás; De, Sourav; Székely, Edit; Bombicz, Petra
Abstract : The number of crystal structures of diastereomeric salt pairs and especially of double salts is limited in the literature. Abstract : The number of crystal structures of diastereomeric salt pairs and especially of double salts is limited in the literature. This work exceptionally presents the structures of two constitutional isomer double salts along with their related diastereomeric salt pairs, which were successfully crystallized and their structures elucidated presenting two complete sets of chiral systems. These results provide a deeper insight into chiral recognition and contribute to the mastery of synthon engineering. The investigated systems are 1-cyclohexylethylammonium 2-chloromandelate ( S – S, R – S, SS – SR ) and 1-cyclohexylethylammonium 4-chloromandelate ( R – R, S – R, SS – SR ). The crystal structures and the thermal properties of all diastereomers (including the less stable diastereomers) and double salts have been determined and comparatively analysed. In the crystal of five of the six chiral salts, hydrogen bonded layers are formed with the participation of the ionic groups and the hydroxyl group of the mandelate anion. In one structure, the hydrogen bond layers are closed to form tubes. Due to the different position of the chlorine substituent in the two compound families, the halogen interactions are oriented towards the inside of the hydrogen-bonded structures or positioned between the layers and establish a relatively strong connection between them. The two different halogen positions and every possible combinations of configurations in the six investigated salts provide a quite detailed landscape of the effect of stereochemistry on the solid-state structure of the salts.